Thermal decomposition of solid state compounds of lanthanide and yttrium benzoates in CO2atmosphere - Locatelli, J. R.; Siqueira, A. B. [UNESP]; Carvalho, C. T. [UNESP]; Ionashiro, M. [UNESP] (Ecletica Quimica, 2008)
Solid-state Ln-Bz compounds, where Ln stands for trivalent lanthanides and Bz is benzoate have been synthesized. Simultaneous thermogravimetric and differential thermal analysis in a CO2atmosphere were used to study the thermal decomposition of these compounds.
Keywords: Benzoate; CO2atmosphere; Lanthanides; Thermal decomposition